Poly Sulfoxyamine Grafted Chitosan as Bactericidal Dressing for Wound Healing - Jadhav, Rahul Laxman; Yadav, Adhikrao Vyankatrao; Patil, Manisha Vyankatrao (Asian Journal of Chemistry, 2019)
In this study, sulfoxyamine derivative of chitosan was carried out by reaction with thionyl chloride and further treated with ammonia. FT-IR, 1H NMR, elemental analysis and DSC methods are used for confirmation of modification. The results revealed that the modified chitosan exhibits better water solubility than chitosan. The evaluation of the applicability of sulfoxyamine modified chitosan in the treatment of dermal wound in rats was performed by induction of transcutaneous wound. The antibacterial activity was tested on Gram-negative and Gram-positive strains. It was found that the modified chitosan showed grater activity against Gram-negative stains as compared to Gram-positive strains. The superior wound healing and antibacterial activity might be due to the grafting of additional cationic group on the polymeric backbone and their ionic interaction with anionic cell wall of skin or bacteria. Modified chitosan also showed significant physical properties like mucoadhesion and film forming or coating properties. The modified chitosan forms film with good adhesion on wound which will protect the wound and also allows gas exchange. These properties are beneficial for treatment of wounds. Similar to chitosan, modified chitosan showed non-toxicity in skin irritation, oral acute toxicity and cytotoxicity.